2020
DOI: 10.1103/physrevb.101.201301
|View full text |Cite
|
Sign up to set email alerts
|

Ambipolar charge sensing of few-charge quantum dots

Abstract: We demonstrate few-charge occupation of electron and hole quantum dots in silicon via charge sensing. We have fabricated quantum dot (QD) devices in a silicon metal-oxide-semiconductor heterostructure comprising a single-electron transistor next to a single-hole transistor. Both QDs can be tuned to simultaneously sense charge transitions of the other one. We further detect the few-electron and few-hole regimes in the QDs of our device by active charge sensing.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…However, in quantum devices based on CMOS technology, devices are typically unipolar. The limited studies of ambipolar quantum dots typically used transport measurements of a single quantum dot connected to both n-type and p-type ohmics. , Recently, Souza de-Almeda et al demonstrated a device with an n-type dot to read out the charge state of a p-type dot (and vice versa). Now the open question is the feasibility of using ambipolar charge sensing in spin qubit devices at the single hole level.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in quantum devices based on CMOS technology, devices are typically unipolar. The limited studies of ambipolar quantum dots typically used transport measurements of a single quantum dot connected to both n-type and p-type ohmics. , Recently, Souza de-Almeda et al demonstrated a device with an n-type dot to read out the charge state of a p-type dot (and vice versa). Now the open question is the feasibility of using ambipolar charge sensing in spin qubit devices at the single hole level.…”
mentioning
confidence: 99%
“…The limited studies of ambipolar quantum dots typically used transport measurements of a single quantum dot connected to both n-type and p-type ohmics. 14,21−25 Recently, Souza de-Almeda et al 26 hole MOS platform via an adjacent charge sensor. The device shows a hole singlet−triplet relaxation time of 11 μs, which is reported for a known double dot hole occupation of (2,8).…”
mentioning
confidence: 99%
“…In a quasi-two-dimensional (planar) quantum dot,with the strongest confinement along the growth direction, the confinement splits the fourfold degeneracy at the Γ point into light and heavy holes, offering a resilient spin qubit residing in the heavy hole subspace [9,19,20]. Spin blockade detection [21][22][23][24], control over the charge state down to a single hole [25,26], fabrication of arrays [27][28][29], and demonstration of single [30,31] and two-qubit operations [32] are among recent experimental achievements with planar dots. In contrast, the strong confinement-induced spin-orbital mixing in a nanowire geometry [33][34][35] gives large and tunable spinorbit interaction [36][37][38][39] and fast spin manipulation [40,41].…”
mentioning
confidence: 99%
“…21 Such ambipolar quantum dots have been studied via direct electrical transport, and recently, ambipolar charge sensing via single-electron and single-hole charge sensors has been demonstrated. 22 However, readout via gate-based sensors 23 or direct dispersive readout via spin projection in double quantum dots [24][25][26] offers more compact and scalable measurement methodologies with comparable measurement sensitivity and shorter integration time.…”
mentioning
confidence: 99%